2015
DOI: 10.1097/bco.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Autologous mesenchymal stem cell implantation in the management of osteonecrosis of the femoral head

Abstract: Background:The aim of this study was to evaluate the results of implantation of mesenchymal stem cells (MSCs) as treatment for early-stage osteonecrosis of the femoral head (ONFH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Among comparative studies, seven were retrospective comparative studies [13,15,17,25,34,54]: six missed to find any significant difference between treatment and control groups, analyzing clinical scores, radiologic outcomes and failures, and only one [27] reported significantly increased clinical and radiological scores, with fewer failures. Two level II prospective comparative studies [11,39] were found in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Among comparative studies, seven were retrospective comparative studies [13,15,17,25,34,54]: six missed to find any significant difference between treatment and control groups, analyzing clinical scores, radiologic outcomes and failures, and only one [27] reported significantly increased clinical and radiological scores, with fewer failures. Two level II prospective comparative studies [11,39] were found in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Majority of the studies, 20 (40%), used the original “Ficat” classification [ 24 , 27 , 29 , 32 , 34 , 36 , 41 , 46 , 48 52 , 56 59 , 61 , 62 , 67 ]. Ten studies (20%) followed the “Modified Ficat” classification [ 12 , 25 , 31 , 44 , 47 , 54 , 55 , 63 , 65 , 70 ] and other eleven (22%) [ 26 , 28 , 30 , 37 39 , 45 , 60 , 66 , 68 , 69 ] used the ARCO system. Finally, nine studies (18%) [ 12 , 13 , 33 , 35 , 40 , 42 , 43 , 53 , 64 ] applied the “Steinberg/University of Pennsylvania” classification.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were published from 1996 to 2019. Eight of the studies were RCTs, 30 - 36 , 49 seven were retrospective case-control studies, 37 , 39 - 43 , 47 and five were prospective control studies. 38 , 44 - 48 , 48 In each of the included studies, the baseline difference between the intervention group and the control group revealed no statistical significance.…”
Section: Resultsmentioning
confidence: 99%
“…Harris Hip Score: A total of 11 trials 29 , 31 , 32 , 35 - 39 , 41 , 42 , 44 , 48 , 48 reported HHS postoperatively during follow-up. Due to the lack of standard deviation (SD) data for four studies, 30 , 38 , 40 , 42 we only analyzed seven studies 32 , 33 , 36 , 37 , 43 , 45 , 49 involving 474 hips (Intervention = 256, Control = 218). According to the different intervention measures, we divided the studies into four subgroups (cell therapy = 3, 33 , 36 , 43 bone grafting = 2, 32 , 37 porous tantalum rod = 1, 49 and biological materials = 1 45 ).…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation